La riscrittura del testo da specialistico a divulgativo - Maurizio Gotti (Altre Modernità, 2012)
The paper first focuses on the construct of popularisation and its various interpretations in the past few decades and briefly reviews the main studies that have been devoted to the analysis of the discourse of popularisation tracing the main conceptual changes and methodological evolutions. The paper then discusses different views concerning the analysis of the popularising process, starting from the approach which compares it to that of translation. Relevant exemplifications are presented from a case study concerning the ‘translation’ of legal concepts for the lay public in a jury trial. The following approach taken into consideration is the viewing of popularisation as recontextualisation, which implies a process of adaptation of popularising discourse to the appropriateness conditions of the new communicative events and to the constraints of the media employed. Indeed, this new communicative approach generally involves a transformation of the original discourse, as the knowledge to be disseminated is recreated in a different communicative situation for the lay audience. Relevant exemplifications are provided from a case study regarding the explanation of health risks in teen magazines. The paper subsequently highlights the social importance acquired by the phenomenon of popularisation, with the mass media no longer seen as passive mediators of scientific knowledge, but as active participants in the production of novel information and new opinions about science and scientists. Rather than ‘explaining’ science, this new type of popularisation sets out to explain the social meaning of such events, with the consequent creation of interdiscursive texts mixing informative and explanatory discourse with other scientifically-unrelated matters of more general public concern. In this process of interdiscursive expression, the recontextualisation of scientific knowledge may run the risk of deviation and utilization for other ends. In the discussion of this issue, examples are given about the ‘neutrality’ of the presentation of medical facts in consumer information leaflets and patient explanatory material. The final part of the paper highlights the need for the adoption of an integrated approach in the analysis of popularising discourse, so as to clearly identify and carefully describe all the aspects involved in this process.